Mikrobiološka zaščita farmacevtskih izdelkov - Gosenca Matjaž, Mirjam (Farmacevtski vestnik, 2021)
The microbiological quality of pharmaceutical products is one of the key aspects of ensuring quality, safety and efficacy of medicines. Due to strict quality assurance standards in the pharmaceutical industry, it can be considered as self-evident. Yet, as we experienced in the year of the pandemic, nothing really is. This review presents various approaches to microbiological protection of pharmaceutical products with the main emphasis on preservatives posing protection from secondary microbiological contamination of products during their storage, distribution and usage. Finally, case studies of preservatives which safety concerns have been raised up in recent years, are presented. In the case of benzyl alcohol, benzalkonium chloride and benzoic acid/benzoate it resulted in recent revision of medicine labelling by the European Medicines Agency, which highlights the need for continuous careful monitoring and safety risk assessment of preservatives and other excipients, especially for the most vulnerable paediatric group of patients.
Keywords: benzalkonijev klorid; benzilalkohol; Farmacevtska industrija; konzervansi; Mikrobiološka analiza; mikrobiološka kakovost; parabeni